EFFECT OF LIQUID ORGANIC FERTILIZER OF BAT MANURE (Chiroptera sp.) ON THE ABUNDANCE OF Nannochloropsis sp. - Hafizhah Zulfaa; Rita Rostika; Heti Herawati; Roffi Grandiosa Herman (Jurnal Perikanan Unram, 2024)
Nannochloropsis sp. is a seawater phytoplanton that is often used as a natural food in aquaculture. Nannochloropsis sp. has a high nutritional content, including proteins, lipids, omega-3 fatty acids, and essential vitamins and minerals that are important for fish growth. Nannochloropsis sp. culture media using bat manure organic fertilizer can increase the abundance of Nannochloropsis sp. and is economical for aquaculture farmers. Bat manure liquid organic fertilizer which has a natural nutrient content rich in nitrogen, phosphorus, and high potassium is used as a nutrient medium in Nannochloropsis sp. This study consisted of 4 treatments of 3 replicates of bat manure organic fertilizer doses, treatment A at 0 ml/L (control), treatment B at 80 ml/L, treatment C at 100 ml/L, and treatment D at 120 ml/L. The results obtained from this research are the use of different doses of bat manure fertilizer can increase the abundance of Nannochloropsis sp. The best Nannochloropsis sp. abundance value in treatment D (120 ml/L) was 24.99 x 106 cells/ml.